Trace metal fluxes in bulk deposition, throughfall and stemflow at two evergreen oak stands in NE Spain subject to different exposure to the industrial environment - Avila, Anna; Rodrigo, Anselm (Atmospheric Environment, 2004)
We compare here the bulkdeposition, throughfall and stemﬂow ﬂuxes of dissolved trace metals in two holm oak (Quercus ilex L.) forests in the Montseny Mountains (NE Spain) with the aim of: (1) applying different methods to distinguish between dry deposition and canopy leaching and (2) to add to the almost non-existing deposition measurements for dissolved Cu, Pb, Mn, V, Zn, Ni and Cd in two Spanish forests differentially exposed to the urban and industrial environment. No signiﬁcant differences in mean bulkdeposition concentrations or ﬂuxes were found between sites, indicating little differential effect of the urban/industrial environment on bulkprecipitation chemistry. At both sites, throughfall and stemﬂow ﬂuxes increased relative to bulkdeposition for all elements, except for Zn and Cd. The relative contribution of leaching and dry deposition was evaluated through: (1) the seasonal variability of throughfall, (2) regressions of element ﬂuxes on water ﬂux in net throughfall, (3) washing branches and metacrylate plates, and (4) the sequential washing of branches. Results indicated that leaching was the main enrichment process for Mn. For Ni, except the sequential washings, all other evidences also pointed to leaching. For Cu, Pb, Zn, Cd and V there was ample evidence for dry deposition. The fact that Zn and Cd had negative net throughfall ﬂuxes indicated that canopy uptake was greater than deposition (wet plus dry). Net throughfall ﬂuxes pointed to higher dry deposition onto the canopies in the more exposed site, but the occurrence of uptake impeached quantiﬁcation. Therefore, dry deposition was estimated from the recovered quantities from experimental washings of foliage, taken to represent the impaction of small particles onto the canopy. The foliage-wash ﬂuxes were, for Zn, Cu and Pb, respectively, 407, 25 and 16 g ha 1 yr 1 at the sheltered site and 423, 38 and 26 g ha 1 yr 1 at the exposed site. Deposition in bulkprecipitation (wet deposition+an unknown fraction of dry deposition mostly accounted by coarse particles settling gravitationally) was lower: 222, 6.3 and 6.5 g ha 1 yr 1 for Zn, Cu and Pb, respectively, averaged for the two sites
Keywords: Dry deposition; Leaching; Mediterranean forests; surrogate surfaces; throughfall; Trace metals

Trace metal fluxes in bulk deposition, throughfall and stemflow at two evergreen oak stands in NE Spain subject to different exposure to the industrial environment (Atmospheric Environment, 2004)
We compare here the bulkdeposition, throughfall and stemﬂow ﬂuxes of dissolved trace metals in two holm oak (Quercus ilex L.) forests in the Montseny Mountains (NE Spain) with the aim of: (1) applying different methods to distinguish between dry deposition and canopy leaching and (2) to add to the almost non-existing deposition measurements for dissolved Cu, Pb, Mn, V, Zn, Ni and Cd in two Spanish forests differentially exposed to the urban and industrial environment. No signiﬁcant differences in mean bulkdeposition concentrations or ﬂuxes were found between sites, indicating little differential effect of the urban/industrial environment on bulkprecipitation chemistry. At both sites, throughfall and stemﬂow ﬂuxes increased relative to bulkdeposition for all elements, except for Zn and Cd. The relative contribution of leaching and dry deposition was evaluated through: (1) the seasonal variability of throughfall, (2) regressions of element ﬂuxes on water ﬂux in net throughfall, (3) washing branches and metacrylate plates, and (4) the sequential washing of branches. Results indicated that leaching was the main enrichment process for Mn. For Ni, except the sequential washings, all other evidences also pointed to leaching. For Cu, Pb, Zn, Cd and V there was ample evidence for dry deposition. The fact that Zn and Cd had negative net throughfall ﬂuxes indicated that canopy uptake was greater than deposition (wet plus dry). Net throughfall ﬂuxes pointed to higher dry deposition onto the canopies in the more exposed site, but the occurrence of uptake impeached quantiﬁcation. Therefore, dry deposition was estimated from the recovered quantities from experimental washings of foliage, taken to represent the impaction of small particles onto the canopy. The foliage-wash ﬂuxes were, for Zn, Cu and Pb, respectively, 407, 25 and 16 g ha 1 yr 1 at the sheltered site and 423, 38 and 26 g ha 1 yr 1 at the exposed site. Deposition in bulkprecipitation (wet deposition+an unknown fraction of dry deposition mostly accounted by coarse particles settling gravitationally) was lower: 222, 6.3 and 6.5 g ha 1 yr 1 for Zn, Cu and Pb, respectively, averaged for the two sites